Looking on the bright side: the relationships between flourishing and pain-related outcomes among adolescents living with chronic pain - Parsons, RD; McParland, JL; Halligan, SL; Goubert, L; Noel, M; Jordan, A (SAGE Publications, 2023)
A deficits-based approach to adolescent chronic pain currently dominates the literature, to the exclusion of positive approaches, such as flourishing. Addressing this knowledge gap, this study examined the relationships between flourishing and pain-related outcomes in adolescent chronic pain. Seventy-nine adolescents aged 11-24 years were asked to complete self-report measures of three domains of flourishing and four pain-related outcomes. Correlation coefficients and four hierarchical linear regression analyses were conducted, controlling for age and gender. Flourishing mental health was associated with, and significantly contributed to explaining, anxiety and depressive symptoms, and social and family functioning impairment. Benefit finding and posttraumatic growth were each associated with social and family functioning impairment, while posttraumatic growth was also associated with anxiety and depressive symptoms. Additionally, benefit finding significantly contributed to explaining pain intensity. Study findings underscore the importance of assessing the relationships between flourishing and pain-related outcomes in adolescents with chronic pain.